Optimization of Bacillus cereus Fermentation Process for Selenium Enrichment as Organic Selenium Source - Chen, Xujun; Li, Shuyi; Cong, Xin; Yu, Tian; Zhu, Zhenzhou; Barba, Francisco J.; Marszalek, Krystian; Puchalski, Czesław; Cheng, Shuiyuan (Frontiers in Nutrition, 2020)
Selenium is an essential trace element and micronutrient for human health. Application of organic selenium in plant and microorganism as trace element supplement is more and more attracting. In this study, Bacillus cereus, an important probiotic, was used for selenium enrichment with sodium selenite as selenium source. The growth curve of Bacillus cereus was investigated and the concentration of selenium for Bacillus cereus fermentation was selected as 150 μg/mL. With application of response surface methodology, the optimal fermentation conditions were obtained as follows: inoculation quantity of 7%, culture temperature of 33°C and shaking speed of 170rpm, leading to the maximal selenium conversion ratio of 94.3%±0.2%. Field emission scanning electron microscope and energy dispersive spectrometry evidenced that inorganic selenium had been successfully transformed. This study may contribute to get a strain with high Se conversion ratio, so as to extract organic selenium in the form of selenoprotein and used for further application.